2006
DOI: 10.2353/ajpath.2006.050600
|View full text |Cite
|
Sign up to set email alerts
|

A Soluble BAFF Antagonist, BR3-Fc, Decreases Peripheral Blood B Cells and Lymphoid Tissue Marginal Zone and Follicular B Cells in Cynomolgus Monkeys

Abstract: BAFF (also known as BLyS), a member of the tumor necrosis factor superfamily, plays a critical role in the maturation and development of B cells. BAFF has three receptors on B cells, the most crucial of which is BR3. In this study, we demonstrate the biological outcome of BAFF blockade in cynomolgus monkeys using a soluble fusion protein consisting of human BR3 and human IgG1 Fc. In vitro, BR3-Fc blocked BAFF-mediated survival and proliferation of cynomolgus monkey B cells. Weekly treatment of cynomolgus monke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 58 publications
(78 reference statements)
4
55
0
3
Order By: Relevance
“…BAFF blockade could result in B-cell reduction in animal models. 36,37 Recent clinical trials with BAFF blockade have shown clinical benefit in SLE and RA. 38,39 Treatment of lupus-prone New Zealand black/white F1 mice with both BR3-Fc and TACI-Ig significantly decreased the proteinuria and glomerular damage in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…BAFF blockade could result in B-cell reduction in animal models. 36,37 Recent clinical trials with BAFF blockade have shown clinical benefit in SLE and RA. 38,39 Treatment of lupus-prone New Zealand black/white F1 mice with both BR3-Fc and TACI-Ig significantly decreased the proteinuria and glomerular damage in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Several BAFF-targeted agents are currently being pursued in clinical development for both autoimmune disease and hematologic malignancies. [13][14][15] However, BR3 is the principal receptor responsible for mediating BAFF-dependent B-cell survival effects. [1][2][3]16 Thus, targeting BR3 directly with an antibody, unlike the ligand-directed approaches, would disrupt the BAFF/BR3 axis specifically and leave BAFF free to signal through its other receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The PD marker measured in this study was absolute peripheral blood B cell counts because by neutralizing BAFF, we expect B cell counts to be reduced (Vugmeyster et al, 2006;Lin et al, 2007). CD19 is expressed on mouse B-lineage cells throughout their development from the early pro-B cell stages onward and was used to gate B cells from the lymphocyte population.…”
Section: Resultsmentioning
confidence: 99%
“…BR3-BAFF interaction seems to be particularly important for the regulation of B cell survival and maturation in the spleen (Ng et al, 2004). Prevention of BAFF binding to BR3 on B cells by neutralizing BAFF via BR3-Fc results in notable peripheral and tissue B cell reduction in rodents and monkeys due to apoptosis (Vugmeyster et al, 2006;Lin et al, 2007). BR3-Fc consists of two polypeptide chains, each containing 299 amino acids, with sequences from the extracellular domain of the human BAFF receptor BR3 and the Fc domain of human IgG1.…”
mentioning
confidence: 99%